Beyond the Bucket: Factors Influencing Customer Satisfaction at KFC Malaysia - Lok Yee Huei; Yi Jing Chow; Zi Tian Chin; Shuchang Cui; Darshana A/P Ramis; Medha Rastogi; Manav Panjwani; Daisy Mui Hung Kee (Advances in Global Economics and Business Journal, 2026)
Customer satisfaction is important because it can improve customer loyalty, reduce customers loss, and provide the management teams with insights to keep the business going. This study aims to examine how service quality, price fairness, and brand image will affect customer satisfaction at KFC Malaysia. A quantitative research design was used, and data were collected from KFC customers in Malaysia using an online survey. Data were collected from 200 respondents and analyzed to test the proposed hypothesis. The findings reveal that service quality and brand image have a positive and significant effect on customer satisfaction, while price fairness shows a positive but not significant effect on customer satisfaction. The results suggest that customers place more importance on brand image and service experience than price when deciding how satisfied they are. This study suggests that KFC Malaysia should focus on service quality and brand image while maintaining transparent pricing. Overall, this study helps fast-food businesses understand how to improve customer satisfaction and stay competitive in Malaysia.